PENGARUH MODEL CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP KEMAMPUAN KOGNITIF IPA SISWA KELAS V SEKOLAH DASAR - Afni, Sri; Silvinia, Silvinia; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this study was to determine the effect of the use of learning model Children Learning In Science (CLIS) on students' cognitive abilities in science teaching in elementary school. The type of this research is Pseudo Experimental Research, with Posttest only control group design. The population in this study were students of grade V SDN 06 Pauh Lubuk Sikaping and determined by total sampling technique. The result of data calculation using t-test at level α 0,05 obtained t count> ttable that is 3,964> 1,67. It can be concluded that there is a significant influence between the use of learning model of Children Learning In Science (CLIS) on students' cognitive abilities in science learning in class V SDN 06 Pauh Lubuk Sikaping.